Serum Inflammatory Factor Profiles in the Pathogenesis of High-Altitude Polycythemia and Mechanisms of Acclimation to High Altitudes. (26th August 2021) - Yi, Hai; Yu, Qianjin; Zeng, Dongfeng; Shen, Zhaohua; Li, Jiali; Zhu, Lidan; Zhang, Xi; Xu, Quanhong; Song, Hu; Kong, Peiyan
Abstract : High-altitude polycythemia (HAPC) is a common aspect of chronic mountain sickness (CMS) caused by hypoxia and is the main cause of other symptoms associated with CMS. However, its pathogenesis and the mechanisms of high-altitude acclimation have not been fully elucidated. Exposure to high altitude is associated with elevated inflammatory mediators. In this study, the subjects were recruited and placed into a plain control (PC) group, plateau control (PUC) group, early HAPC (eHAPC) group, or a confirmed HAPC (cHAPC) group. Serum samples were collected, and inflammatory factors were measured by a novel antibody array methodology. The serum levels of interleukin-2 (IL-2), interleukin-3 (IL-3), and macrophage chemoattractant protein-1 (MCP-1) in the eHAPC group and the levels of interleukin-1 beta (IL-1 beta), IL-2, IL-3, tumor necrosis factor-alpha (TNF-alpha), MCP-1, and interleukin-16 (IL-16) in the cHAPC group were higher than those in the PUC group. More interestingly, the expression of IL-1 beta, IL-2, IL-3, TNF-alpha, MCP-1, and IL-16 in the PUC group showed a remarkable lower value than that in the PC group. These results suggest that these six factors might be involved in the pathogenesis of HAPC as well as acclimation to high altitudes. Altered inflammatory factors might be new biomarkers for HAPC and for high-altitude acclimation.